Revision of the neotropical jumping plant-louse genus Mastigimas (Hemiptera, Psylloidea) attacking Cedrela and Toona species (Meliaceae) - Burckhardt, Daniel; Queiroz, Dalva L.; Drohojowska, Jowita (Zootaxa, 2013)
The small Neotropical genus Mastigimas with five described species is revised. Three new species are added: Mastigimas colombianus sp. n. from Colombia on Cedrela montana, M. drepanodis sp. n. from Brazil (Paraná) on C. fissilis and M. reseri sp. n. from Jamaica collected in light traps. Another two species are recorded from Brazil and Colombia, respectively, which are not formally described due to insufficient material. The new species are described, and illustrations and identification keys are provided for all species. The last instar immatures are described for five species. The phylogeny within Mastigimas is analysed, and the biogeographic and host plant relationships are discussed.